2007
DOI: 10.1038/sj.mp.4001975
|View full text |Cite
|
Sign up to set email alerts
|

Convergent genetic modulation of the endocrine stress response involves polymorphic variations of 5-HTT, COMT and MAOA

Abstract: Highly prevalent stress-related disorders such as major depression (MD) are characterised by a dysregulation of the neuroendocrine system. Although heritability for these disorders is high, the role of genes in the underlying pathophysiology is poorly understood. Here, we show that polymorphic variations in genes coding for serotonin transporter (5-HTT), catechol-Omethyl transferase (COMT) and monoamine oxidase A (MAOA) as well as sex differences influence the regulation of hypothalamic-pituitary-adrenal (HPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 32 publications
7
127
4
3
Order By: Relevance
“…These include polymorphisms or expression of BDNF (Krishnan et al, 2007), GABRA2 (Nelson et al, 2009), 5-HT1A receptors, dopamine or serotonin transporters (Segman et al, 2002;Kilpatrick et al, 2007;Stein et al, 2009;Wald et al, 2013), catechol-O-methyl transferase (COMT; Jabbi et al, 2007;Kolassa et al, 2010), glucocorticoid receptors and factors that modulate them such as FK506-binding protein (FKBP5;Binder et al, 2008;Derijk and de Kloet, 2008;McGowan et al, 2009;Sarapas et al, 2011), and methylation of corticotrophin-releasing factor (CRF) receptor DNA (Elliott et al, 2010). Several genetically distinct rodent lines are differentially resistant/vulnerable to the effects of stress (Razzoli et al, 2011;Savignac et al, 2011;Camp et al, 2012;Fuchsl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These include polymorphisms or expression of BDNF (Krishnan et al, 2007), GABRA2 (Nelson et al, 2009), 5-HT1A receptors, dopamine or serotonin transporters (Segman et al, 2002;Kilpatrick et al, 2007;Stein et al, 2009;Wald et al, 2013), catechol-O-methyl transferase (COMT; Jabbi et al, 2007;Kolassa et al, 2010), glucocorticoid receptors and factors that modulate them such as FK506-binding protein (FKBP5;Binder et al, 2008;Derijk and de Kloet, 2008;McGowan et al, 2009;Sarapas et al, 2011), and methylation of corticotrophin-releasing factor (CRF) receptor DNA (Elliott et al, 2010). Several genetically distinct rodent lines are differentially resistant/vulnerable to the effects of stress (Razzoli et al, 2011;Savignac et al, 2011;Camp et al, 2012;Fuchsl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this investigation are studies that have begun to shed light on the epitasis between COMT and other genes in the context of phenotypes such as novelty seeking (Benjamin et al, 2000), extraversion (Golimbet, Alfimova, Gritsenko, & Ebstein, 2007) and the stress response (Jabbi et al, 2007). Moreover, a recent functional magnetic resonance imaging study of working memory revealed that the COMT Met homozygous genotype mediated against inefficient task related brain activations observed in the combined presence of glutamate receptor mgluR3 (GRM3) and the homozygous COMT Val genotype (Tan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jabbi et al (2007) and Gotlib et al (2008) found larger cortisol responses to a stressor in homozygous carriers of the S allele (Gotlib et al, 2008;Jabbi et al, 2007). We recently reported that newborns with two S alleles exhibit the highest cortisol response after a physical stressor (Mueller et al, 2010).…”
Section: -Httlpr Sles and Stressmentioning
confidence: 95%